2009
DOI: 10.1242/dev.034454
|View full text |Cite
|
Sign up to set email alerts
|

The apicobasal polarity kinase aPKC functions as a nuclear determinant and regulates cell proliferation and fate duringXenopusprimary neurogenesis

Abstract: During neurogenesis in Xenopus, apicobasally polarised superficial and non-polar deep cells take up different fates: deep cells become primary neurons while superficial cells stay as progenitors. It is not known whether the proteins that affect cell polarity also affect cell fate and how membrane polarity information may be transmitted to the nucleus. Here, we examine the role of the polarity components, apically enriched aPKC and basolateral Lgl2, in primary neurogenesis. We report that a membrane-tethered fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 46 publications
10
39
0
Order By: Relevance
“…S3, 2dox, yellow arrows indicate positive PDM puncta). aPKCi was also found in the nucleus, which has been reported previously in other cell types (Sabherwal et al, 2009). Some T567-phosphorylated ezrin was randomly localized to the cell cortex (supplementary material Fig.…”
Section: Resultssupporting
confidence: 85%
“…S3, 2dox, yellow arrows indicate positive PDM puncta). aPKCi was also found in the nucleus, which has been reported previously in other cell types (Sabherwal et al, 2009). Some T567-phosphorylated ezrin was randomly localized to the cell cortex (supplementary material Fig.…”
Section: Resultssupporting
confidence: 85%
“…1, could occur by two types of mechanism: ingression (delamination) of epithelial cells to deeper layers, or an increase in cell divisions with a horizontal cleavage plane in which one of the two daughters lies below, rather than within, the epithelium. Cell ingression from the superficial epithelial layer has previously been seen upon overexpression of the basolateral polarity protein Lgl2 (Sabherwal et al, 2009). PAR-1 perturbation produced by expression of a dominant-negative PAR-1 causes cells to be expelled from cultured mammalian epithelia (Bohm et al, 1997), suggesting that this could be occurring in the superficial ectodermal epithelium.…”
Section: Resultsmentioning
confidence: 94%
“…First, promotion of vertical spindle orientation increases the number of cells that lack apical membrane. Since apical membrane contains aPKC, which is an inhibitor of neurogenesis (Sabherwal et al, 2009), partitioning a daughter cell away from apical membrane is a mechanism for relieving this inhibition and is thus a novel form of aPKC antagonism. It is important to note that physical displacement of superficial cells into deep positions, either by dissection or by overexpression of Lgl2, is not sufficient for neurogenesis (Chalmers et al, 2002;Sabherwal et al, 2009;Strauss et al, 2006), and so it is this partitioning rather than the deep non-epithelial microenvironment that is important.…”
Section: Research Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there seems to be a fundamental link between apicobasal polarisation and the proliferative properties of neural progenitors, from Drosophila to mammals, the mechanistic links between these two processes are not well defined. When an activated version of the apicobasal polarity regulator atypical protein kinase C (aPKC) is expressed, neurogenesis is blocked and proliferation enhanced (Sabherwal et al, 2009). Nancy Papalopulu reported that aPKC mediates these effects by binding to, and phosphorylating, a key component of the cell cycle.…”
Section: Regulation Of the Cell Cycle And Differentiation By Signallimentioning
confidence: 99%